2014
DOI: 10.1177/1084822314563331
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning Among Elderly Care Managers Inspires Projects That Take Older People’s Perspectives Into Account

Abstract: When the national core value system was introduced in Sweden, care professionals were challenged to be part of a paradigm shift by changing their perspective, from regarding older people like passive recipients of societal efforts to treating them as active subjects and taking their preferences and wishes into consideration as well. To realize this shift in attitudes and behavior, an interprofessional blended education course was offered. The present study explored the utility of the blended educational approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…One purpose of professional training is for theoretical knowledge to contribute to quality development in everyday practice (Schatzki, ; Umb Carlsson et al, ). The present study showed that a quarter of the project plans were never commenced.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One purpose of professional training is for theoretical knowledge to contribute to quality development in everyday practice (Schatzki, ; Umb Carlsson et al, ). The present study showed that a quarter of the project plans were never commenced.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have shown that the training stimulated thoughts and ideas related to the national core value system (cf. Umb Carlsson et al, ) and that most participants wanted to implement their ideas. The present results revealed that environmental factors could act as facilitating or obstructing factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations